Nutritional therapy for MRSA sepsis complicated with pulmonary embolism in children under limited energy and nutrient conditions: a case report - Kong, Lin; Xia, Li; Zhou, Fang; Tan, Tian; Gao, Zhongmin; Zhou, Bo; Jiang, Yao; Liu, Chengjun; Pi, Dandan (Frontiers in Nutrition, 2025)
The nutritional treatment of methicillin-resistant Staphylococcus aureus sepsis combined with pulmonary embolism presents considerable challenges due to the risks associated with tube placement, coagulation disorders, severe infections, digestive limitations, and fluid restrictions in pediatric patients. This report discusses the case of an approximately 13-year-old female patient admitted with symptoms of right lower limb pain, fever, and cough accompanied by shortness of breath. The patient was assessed to be at moderate risk of malnutrition. In the early stages of treatment, permissive low-calorie enteral nutrition was administered alongside clinical interventions such as anti-infection therapy, anticoagulation, and empyema drainage. In the later stages, supplementary parenteral nutrition therapy was introduced, with careful monitoring of fluids restrictions, infection control, and coagulation index improvements. The patient’s condition improved significantly, and the wounds on the right chest and back healed well. A retrospective review of the literature over the past decade was conducted using domestic and international databases, alongside an analysis of current guidelines for nutritional support in critically ill children.